A dimensão subjetiva da violência da escola: um estudo sobre significações de alunos sobre práticas coercitivas no processo educacional - Bravim, Ana Clara Fernandes (2021)
This study investigated the subjective dimension of the violence at school, by means of the research of the significances of the experience in the school environment of students in the public schools in the city of São Paulo. We understand the schooling process as a social and historical process, and, that it can only be understood in this reality. For years, the Brazilian schooling process had the presence of coercive practices in the educational institutions, lately, these practices have been left behind, committing the education to a more democratic vision. Therefore, this research was based on the criticism of the theoretical references of the social-historical psychology; We used the nuclei of meanings, as our instrument of analysis, and, the subjective dimension category as our theoretical source. We talked to 3 people in order to produce information, seeking elements of significance - senses and meanings - from the youngsters around their school experience. We discussed about their relation with the other students, but we enhanced the discussion about the relation between teacher and student, which offers us material for learning and understanding the phenomenon of violence at school. In order to understand the significance elements, after reading the information produced, we constituted significances cores. Based on the analysis, the violence at school produces and reproduces the naturalization of violent phenomenon in that environment, based on the feeling of exteriority of the Schooling process, therefore, the violence from the institutions creates social responsibilities to the students. We highlight that the power of transformation lies on the fact that they enjoy school